2018
DOI: 10.1037/amp0000120
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating pipeline progress from doctoral degree to first job.

Abstract: The sequence of professional development within psychology from doctoral education to first job represents a period of remarkable professional and personal growth for each trainee. However, this sequence also contains a variety of barriers that hinder progress through the pipeline. The myriad individual-, program-, and system-level barriers encountered by trainees in health service/other applied service psychology and in research basic/applied psychology are identified. To actively and systematically facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 91 publications
(165 reference statements)
0
18
0
Order By: Relevance
“…Feedback should be clear and consistent throughout the process. Trainees' may feel helpless and fear negative "halo" perceptions among trainers, worried about being highly scrutinized for the remainder of their time in the program and beyond, concerned about the impact diversity might have had related to their identification with PPC and/or remediation plan progress, and stressed about being able to move successfully through the professional pipeline (Kaslow, Bangasser, et al, 2018).…”
Section: Assessing the Outcomes Of The Remediation Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedback should be clear and consistent throughout the process. Trainees' may feel helpless and fear negative "halo" perceptions among trainers, worried about being highly scrutinized for the remainder of their time in the program and beyond, concerned about the impact diversity might have had related to their identification with PPC and/or remediation plan progress, and stressed about being able to move successfully through the professional pipeline (Kaslow, Bangasser, et al, 2018).…”
Section: Assessing the Outcomes Of The Remediation Planmentioning
confidence: 99%
“…Remediation strategies behaviorally based in clear language provide concrete methods for improvement. Although not exhaustive, Table 2 offers examples of strategies for a remediation plan to (1) increase knowledge, (2) enhance skills, and (3) deepen self-awareness (Hauer et al, 2009; Kalet et al, 2016; Kaslow, Bangasser, Grus, McCutcheon, & Fowler, 2018; Kaslow et al, 2007b; Kress & Protivnak, 2009; Regan et al, 2016; Torbeck & Canal, 2009; Ziring et al, 2015). The interventions selected may be specific to the underlying causes of the PPC (e.g., if substance abuse prevents them from completing coursework, treatment and a leave of absence may be appropriate).…”
Section: The Remediation Processmentioning
confidence: 99%
“…The psychology pipeline represents the successive educational, training, and employment transitions extending from undergraduate enrollment to formal employment (Kaslow, Bangasser, Grus, McCutcheon, & Fowler, 2018). To date, there is very little research published on specific work-family conflicts faced by psychologists during their movement through the pipeline.…”
mentioning
confidence: 99%
“…The most recent data, from 2016, reflect 118,000 Bachelor's degrees, 27,645 master's degrees and 6,600 doctoral degrees in psychology (U.S. Department of Education, National Center for Educational Statistics, 2018). At the same time, for decades, the field of psychology has recognized a critical shortage of professionals from diverse racial, ethnic, and socioeconomic backgrounds across various stages of training, practice, and leadership (see, e.g., Kaslow, Bangasser, Grus, McCutcheon, & Fowler, 2018;Lott & Rogers, 2011). Indeed, the APA Education Directorate's Graduate Study in Psychology, 2017 Summary Report (Cope, Michalski, & Fowler, 2016) found increases in enrollment over a 10-year timeframe across most racial and ethnic minority groups.…”
Section: The Need For Mental Health Providersmentioning
confidence: 99%